2013
DOI: 10.1186/1471-2180-13-36
|View full text |Cite
|
Sign up to set email alerts
|

Clustering subspecies of Aeromonas salmonicida using IS630typing

Abstract: BackgroundThe insertion element IS630 found in Aeromonas salmonicida belongs to the IS630-Tc1-mariner superfamily of transposons. It is present in multiple copies and represents approximately half of the IS present in the genome of A. salmonicida subsp. salmonicida A449.ResultsBy using High Copy Number IS630 Restriction Fragment Length Polymorphism (HCN-IS630-RFLP), strains of various subspecies of Aeromonas salmonicida showed conserved or clustering patterns, thus allowing their differentiation from each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…More complex rearrangements involving other ISs are also suspected. IS 630 copies might also play a role in the genetic organization of the injectisome because they are frequently associated with T3SS loci in A. salmonicida (Studer et al ., ) (http://onlinelibrary.wiley.com/doi/10.1111/1751-7915.12091/suppinfo) but also in other pathogenic bacteria using such secretion systems (Haneda et al ., ; Correa et al ., ; Stavrinides et al ., ). The cluster of T3SS genes can also be integrated in the chromosome of some strains of certain species of Aeromonas .…”
Section: Genetic Organization Of the A Salmonicida T3ssmentioning
confidence: 99%
“…More complex rearrangements involving other ISs are also suspected. IS 630 copies might also play a role in the genetic organization of the injectisome because they are frequently associated with T3SS loci in A. salmonicida (Studer et al ., ) (http://onlinelibrary.wiley.com/doi/10.1111/1751-7915.12091/suppinfo) but also in other pathogenic bacteria using such secretion systems (Haneda et al ., ; Correa et al ., ; Stavrinides et al ., ). The cluster of T3SS genes can also be integrated in the chromosome of some strains of certain species of Aeromonas .…”
Section: Genetic Organization Of the A Salmonicida T3ssmentioning
confidence: 99%
“…Furthermore, many plasmid variants display transpositions or IS-mediated recombinations when compared to their reference (IS AS 5 in many plasmids, IS Ec 9 in pSN254b) (Attéré et al, 2015; Najimi et al, 2009; Trudel et al, 2013; Vincent et al, 2014b). Given the high number of ISs in the genome of this bacterium (Studer, Frey & Vanden Bergh, 2013; Vincent et al, 2016b), we hypothesize that ISs play a role in plasmid reshaping (Tanaka, Frenette & Charette, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…A low quantity of amoebae was able to create a phagocytic plaque on K. aerogenes (the positive control) while only a high quantity of D. discoideum cells was required to observe amoebal growth on JF2480 (Figure 3). Thus, bacterial virulence assays conducted on JF2480 revealed that this strain is virulent when facing D. discoideum even in absence of a complete T3SS compared to K. aerogenes bacterium known to be totally avirulent [47]. Other mesophilic A. salmonicida strains do not possess a complete T3SS.…”
Section: Resultsmentioning
confidence: 92%